Upper Gastrointestinal Endoscopy Detection of Synchronous Multiple Primary Cancers in Esophagus and Stomach: Single Center Experience from China - Rui Wang; Mo-Jin Wang; Jin-Lin Yang; Cheng-Wei Tang (Gastroenterology Research and Practice)
The present study was undertaken to clarify the prevalence and clinicopathological features of synchronous multiple primary cancers (SMPCs) under upper gastrointestinal endoscopic examination. We enrolled 45,032 consecutive patients who underwent upper gastrointestinal endoscopic examination for digestive disease from January 2006 to December 2007 in our hospital and analyzed the clinicopathological features of SMPCs in esophagus and stomach. SMPCs are defined as two or over two different cancerous lesions developing in the same or other organs within 6 months. SMPCs were identified in 46 patients (0.1%). The gender ratio was 5.6 : 1 (male/female) and the mean age was 59.4 years. Synchronous esophageal and gastric cancers were the most frequent, being seen in 32 patients (0.07%). The most common histological types of SMPCs were squamous cell carcinoma in esophagus and adenocarcinoma in stomach, respectively. There were 27 (59%) SMPCs patients who had the history of simultaneous exposure to tobacco smoking and alcohol drinking. Additionally, 32 (78%) esophageal squamous cell cancers were associated with tobacco use. And 23 adenocarcinomas of the stomach were associated with Helicobacter pylori infection.